The Influence of Exo as Brand Ambassador and Scarlett's Brand Image on Scarlett Brand Purchasing Decisions - Surianto Surianto; Gracia Johana (Journal of Social Science, 2024)
Technological developments have had a significant impact on various sectors, including economics, politics and business competition in this era of globalization. The internet, as an example of rapid technological development, is a major driver of progress in various aspects of human life. Competition in the business environment is increasing along with developments in technology and knowledge, so entrepreneurs need to continue to design effective marketing strategies. One of the key aspects of marketing strategy is the ability to understand and adapt to constantly changing market trends. In the context of social media marketing, the use of Brand Ambassadors is a tactic often used by e-commerce to increase the popularity of their platforms. This research aims to evaluate the influence of EXO as a Brand Ambassador and the Scarlett brand image on consumer purchasing decisions. The research method used is quantitative with survey techniques using questionnaires. The research results show that both EXO as a Brand Ambassador and the Scarlett brand image have a significant positive influence on consumer purchasing decisions.